The personnel development training programme effectiveness factor towards work motivation among public servants: a case study at Jabatan Pelajaran Negeri Kedah / Noor Aznida Azmar and Nabilah Hanun Mohamad Rathi - Azmar, Noor Aznida; Mohamad Rathi, Nabilah Hanun (2013)
This study is conducted as an attempt to understand the Personnel Development Training Programme effectiveness factors towards public servants’ work motivation at Jabatan Pelajaran Negeri Kedah. A total of 175 respondents are selected to become the respondents in this study to answer the questionnaires given. Based on the sample size, the researchers are going to identify the relationship between variables by using Pearson correlation. Besides that, the most influential Personnel Development Training Programme effectiveness factor that lead to public servants’ work motivation will be analyze based on the Multiple Regression Analysis. In addition, the researchers also aim to identify the level of public servant work motivation based on descriptive analysis. The results of the study are expected to guide the top management of JPN Kedah in order to provide more effective training program and better understanding on the concept of public servant work motivation.